Case report: obstruction in the right ventricular outflow tract due to hemolymphangioma - Chen, Bo; Fan, Ting; Cao, Yong; Hu, Lian; Yu, Guanshui (Frontiers in Cardiovascular Medicine, 2023)
Cardiac masses commonly involve primary tumors, metastatic diseases, and nonbacterial thrombotic and infective endocarditis. Myxomas are the most common primary tumors, accounting for 75%. Hemolymphangiomas are a group of congenital vascular and lymphatic malformations that originate from the mesenchyme, with an incidence rate of 0.12%–0.28% per year. Hemolymphangiomas have been found in the rectum, small intestine, spleen, liver, chest wall, and mediastinum but have not yet been reported in the ventricular outflow tract in the heart. This case report is of a patient with hemolymphangioma in the right ventricular outflow tract. The tumor was successfully resected, and the patient was followed up for 18 months and did not exhibit tumor recurrence.